The impacts of website information disclosure on organizational attractiveness: the moderating effect of corporate social responsibility performance - Fei-Chun Cheng; Chao-Chan Wu; Ching-Feng Wu (Humanities & Social Sciences Communications)
Abstract With the increasing emphasis on sustainability, green recruitment has become an emerging issue. When job seekers gain an understanding of a company through its website, the information presented will affect their perception of the company. This study focuses on corporate social responsibility (CSR) website disclosure and examines whether the multidimensional construct of CSR information disclosed on a company’s website affects organizational attractiveness. It also investigates the moderating effect of actual CSR performance on the relationship between CSR website disclosure and organizational attractiveness. There are two levels in this study: organizational and individual. At the organizational level, 30 listed companies (in the semiconductor, electronics, and optoelectronics fields) from the Digital Times’ Top 100 Favorite Companies were selected as a sample. At the individual level, participants were invited to complete a questionnaire for data collection after viewing the target organization’s CSR website. A total of 245 students participated in this study. Hierarchical linear modeling was used for data analysis. The results show that environmental protection and energy practice disclosure is positively related to organizational attractiveness, including intention to pursue and Reputation. Employee rights and benefits on websites are also found to be positively related to organizational attractiveness, that is, intention to pursue. Inappropriate disclosure of product and service information on the CSR website can lead to suspicion among job seekers, which is detrimental to the intention to pursue. There is also a moderating effect between the organization’s actual corporate social responsibility (CSR) performance, website disclosure of CSR practices and organizational attractiveness. Previous research has predominantly focused on social responsibility activities. The findings of this study highlight the importance of web page disclosure, providing valuable insights for managerial practice and contributing to the enrichment of related theoretical literature.